Energy evolution characteristics and failure mechanism of coal confined by CFRP jackets subjected to different loading rates - Qingwen Li; Mengjiao Xu; Wenxia Li; Chuangchuang Pan; Mengmeng Yu (Polymer Testing)
To reveal the improvement effects of Carbon fiber reinforced polymer (CFRP) jackets on the strength and deformation characteristics of coal samples, and the energy transformation mechanism during the failure process of coal samples under different loading rates. In this study, uniaxial compression tests were conduct on 28 coal samples, the results indicated that both the loading rate and the number of CFRP layers significantly influenced the energy evolution process of the coal samples. The total energy growth ratio of coal samples confined by single and double layer of CFRP jackets ranging from 11.86 to 23.46 and 32.002–56.066, respectively, with the total energy at failure of the double layer samples being 1.8 times that of the single layer ones. The number of CFRP layers significantly enhances the total energy at the peak point and its growth ratio of the coal samples. At the minimum (maximum) loading rate, the growth ratio of the dissipation energy rate at the peak point decreases with the increase of CFRP layers. Additionally, the value at the maximum rate is approximately 6.03–8.87 times greater than that at the minimum rate. The elastic energy consumption ratio exhibited a ‘fishhook-shaped’ trend as axial deformation increased. The use of CFRP jackets can effectively improve the energy storage mechanism of coal samples. Therefore, studying the energy dissipation and failure behavior of CFRP confined coal samples subjected to different loading rates is crucial for reducing the risk of accidents caused by coal pillar instability.